E-Modul Interaktif Berbasis Articulate Storyline untuk Meningkatkan Kemampuan Penalaran Berbasis Bukti - Astutik, Windy Amelia; Supeno, Supeno; Wicaksono, Iwan; Prasetiyaningsih, Anis (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to examine the quality of interactive e-modules based on articulate storyline to improve the evidence-based reasoning abilities of junior high school students in learning natural sciences. The type of this research is research and development (Research and Development) with the ADDIE development model. The stage of e-module development consist of analysis, design, development, implementation, and evaluation. The data collection techniques include interviews, observation, and documentation. The data from student response questionnaires and observation of learning implementation were analyzed with percentage analysis. The data of evidence-based reasoning ability were analyzed with n-gain analysis. The results showed that the validity of the interactive e-module was 94.25%, with a very valid category. Student response to interactive e-modules was 81.88% with positive criteria, and the implementation of learning using interactive e-modules was 90% with perfect types. The n-gain analysis show that learning using interactive e-modules can increase evidence-based reasoning abilities by 0.31 in the moderate category.